Pengaruh Kompensasi dan Gaya Kepemimpinan Demokrasi Terhadap Retensi Karyawan - Prawira, Muhammad Fajar; S. Marinda, Vina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Companies that want to continue to survive in business competition need Human Resources (HR) or quality employees. To retain quality employees so they don't leave the company, employee retention is needed because the key to the success of an organization depends on employee retention. Employee retention is a strategy carried out by companies to retain employees who have good performance to remain loyal and stay in the company. This study aims to analyze the effect of compensation and democratic leadership style on employee retention at a pharmaceutical company in Bogor Regency. The sample in this study was 82 employees who worked at a pharmaceutical company in Bogor Regency. The analysis technique in this study used multiple linear regression analysis. Testing the model in this study is using the F-test while testing the hypothesis using the t-test. The results showed that the compensation variable had a significant effect on employee retention at a pharmaceutical company in Bogor Regency. Meanwhile, the democratic leadership style variable has no effect on employee retention at a pharmaceutical company in Bogor Regency.